Crystal-plane effect of Cu2O templates on compositions, structures and catalytic performance of Ag/Cu2O nanocomposites. Issue 12 (6th March 2019) - Zhang, Zhenhua; Song, Rui; Yu, Zongyou; Huang, Weixin
Abstract : The compositions, structures and catalytic performance of acquired Ag/Cu2 O nanocomposites are strongly dependent on the crystal plane of employed Cu2 O solid templates. Abstract : Various Ag/Cu2 O nanocomposites were prepared via the galvanic replacement reaction involving AgNO3 reacting respectively with uniform Cu2 O cubes and octahedra. Their compositions and structures were comprehensively characterized microscopically and spectroscopically. The results reveal that the crystal plane of employed Cu2 O solid templates determines the compositions and structures of the resulting Ag/Cu2 O nanocomposites. A smooth surface mixed with nanoneedles or nanosheets of Ag/c-Cu2 O structures was fabricated on Cu2 O cubes while flocculent Ag/o-Cu2 O structures were fabricated on Cu2 O octahedra. The catalytic performance of Ag/Cu2 O nanocomposites were evaluated in CO oxidation with excess O2 . In situ surface restructuring occurs on various Ag/Cu2 O nanocomposites to form Ag–CuO/Cu2 O nanocomposites. The catalytic activity of the resulting Ag–CuO/Cu2 O nanocomposites depends on the structures of CuO and Ag that are affected by the original crystal plane of Cu2 O solid templates and the Ag loading. These results broaden the crystal-plane effect of Cu2 O nanocrystals as solid templates for synthesis of multicomponent nanocomposites via liquid–solid interfacial reactions.